Optimization of CdS/TiO2 Nanotube-Array Composite Photocatalysts Prepared by Electrodeposition - Wang, C.T.; Zhang, W.K.; Huang, H.; Wu, J.M.; Gan, Y.P.; Tao, X.Y. (Asian Journal of Chemistry, 2014)
Titania nanotube arrays were prepared by titanium anodizing, then CdS/TiO2 nanotube arrays composite photocatalysts were prepared by an AC electrodeposition method for different times. The morphology and crystal structure of the CdS/TiO2 composite photocatalysts were characterized by SEM and XRD. The photoelectrochemical properties of the composites were investigated by means of UV-visible absorption spectra and photocurrent measurements. The photocatalytic activity was evaluated by the degradation of methyl orange under UV-visible light irradiation. The results show that there is an optimum deposited time for the highest photocatalytical activity of the CdS/TiO2 composite photocatalysts under UV-visible light irradiation and the optimum deposited time is determined to 3 min.